A modified ABC algorithm approach for power system harmonic estimation problems - Kabalci, Yasin; Kockanat, Serdar; Kabalci, Ersan (Electric power systems research, 2018)
•A power system harmonic estimator is designed in this study.•Proposed estimator is conducted by using modified ABC optimization algorithm.•Several performance analyses are investigated to verify proposed method.•Proposed system can be securely exploited to estimate power harmonics. Electrical harmonic is an important issue on power quality of electrical systems. Therefore, estimation of power harmonics are essential to design filters to be utilized in electrical power systems for reducing harmonics and their effects on the electrical power systems. In this study, a power system harmonic estimation solution based on modified artificial bee colony (MABC) algorithm have been proposed. The proposed method in this study is different from other hybrid techniques previously reported ones since estimation processes are mainly focused on decreasing computational complexity and time. In order to provide more accurate and comprehensive estimation results for the proposed method, two different experiments are investigated. Obtained results by the performed experiments showed that the proposed harmonic estimator provides several advantages such as offering very low computational time, more accurate estimation of amplitude and phase values for all conditions and low complexity.